0.90(8)+1.04p=0.98(8+p)

Simple and best practice solution for 0.90(8)+1.04p=0.98(8+p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.90(8)+1.04p=0.98(8+p) equation:


Simplifying
0.90(8) + 1.04p = 0.98(8 + p)

Multiply 0.90 * 8
7.2 + 1.04p = 0.98(8 + p)
7.2 + 1.04p = (8 * 0.98 + p * 0.98)
7.2 + 1.04p = (7.84 + 0.98p)

Solving
7.2 + 1.04p = 7.84 + 0.98p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-0.98p' to each side of the equation.
7.2 + 1.04p + -0.98p = 7.84 + 0.98p + -0.98p

Combine like terms: 1.04p + -0.98p = 0.06p
7.2 + 0.06p = 7.84 + 0.98p + -0.98p

Combine like terms: 0.98p + -0.98p = 0.00
7.2 + 0.06p = 7.84 + 0.00
7.2 + 0.06p = 7.84

Add '-7.2' to each side of the equation.
7.2 + -7.2 + 0.06p = 7.84 + -7.2

Combine like terms: 7.2 + -7.2 = 0.0
0.0 + 0.06p = 7.84 + -7.2
0.06p = 7.84 + -7.2

Combine like terms: 7.84 + -7.2 = 0.64
0.06p = 0.64

Divide each side by '0.06'.
p = 10.66666667

Simplifying
p = 10.66666667

See similar equations:

| -4x+14=x-1 | | 2/3(x-4)=5/4-7x | | 5(2x-4)+10=5x+35 | | 5+2r=2r+6 | | 0.98(8)-1.04p=0.98(8+p) | | 3(2x-2)-9=-x+34 | | 7a-3=3+6n | | 30=5(x+2) | | 0.98(8)+1.04p=0.98(8+p) | | 3(2x-1)-3=48 | | 2(x-1)=-x+16 | | -x-9=3x+11 | | -x+47=4(x-2) | | -7x-3x+2=-8 | | 2x^2+4y^2-4x-24y+36=0 | | (2x-3)/7=(3x)/7-2x | | p^3-4p^2-p+4= | | 2.2q-3.9-2.8q=-1.6q-1.8 | | 4n=m(5-n) | | 3x^2-10x-28=0 | | -x^2+14x-57=0 | | -10=30 | | 64=2a+a^2+1 | | 2x^3+x^2-4x-3=0 | | x+4=2(.4x+1.3) | | 15x^3-43x^2+28-4=0 | | 0=60x-3x^2 | | 3x+71=44 | | 4-7f=25 | | 27-3e=18 | | 10+4d=-26 | | x(x-2)=(x+2) |

Equations solver categories